Challenges of Assessment of Learners with Disabilities in Pre and Primary Schools: Experience from Rukwa Region in Tanzania - Mligo, Ignasia; Muhammed, Shehe Abdalla (Departemen Penelitian dan Pengembangan Perkumpulan Program Studi PAUD Indonesia, 2024)
This paper investigated the challenges of assessing learners with disabilities in Tanzanian primary schools. It explored the views of teachers and learners with disabilities regarding the challenges of assessments for learners with disabilities, and what needs to be done to address the situation. This paper reports findings from a qualitative study that employed a case study design in four primary schools in Tanzania. A total of 34 participants were engaged in the study using a purposive sampling strategy: 04 Heads of schools, 10 special needs specialist teachers, 20 pupils with different disabilities, where 09 had hearing impairment, 07 were visually impaired, and 04 had physical disabilities. Data were generated through interviews, focus group discussions, and document reviews. The findings indicated that the assessment of learners with disabilities in Tanzania is still unsatisfactory due to insufficient resources, insufficient supportive infrastructure, poor assessment environment and insufficient experts in the area to support learners with disabilities. Furthermore, the study findings indicated the challenges in curriculum implementation. It is also revealed that pupils with disabilities have their own way of learning, different from pupils without disabilities. According to their nature, teachers use much time to teach them and not easy to finish the syllabus on time, pupils in some cases find some questions whose topics were not covered. This study recommends that there is a need for a forging of partnership between the government and the practitioners. Government policymakers should set clear policies regarding learners with disabilities in diverse aspects such as human, fiscal and time resources. There is also a need for legal frameworks to be in place to protect learners with disabilities from neglect, social stigma and prejudice. Learners with disabilities are to be effectively dealt with, so learners should be empowered to reach their potentials in life.